Ammonia Removal Using Coconut Shell Based Adsorbent: Effect of Carbonization Duration and Contact Time - Oktavitri, Nur Indradewi; Purnobasuki, Hery; Kuncoro, Eko Prasetyo; Purnamasari, Indah (Institut Teknologi Sepuluh Nopember, 2017)
The preparation of adsorbent using activated coconut shell was investigated at carbonization duration and adsorption contact time.Â The coconut shell was activated using physical and chemical activation.Â This research focused on variation of physical activation such as carbonization. The carbonization had two steps, there are high temperature and medium temperature. This research used 500oC at high temperature and 220oC at medium temperature. The duration of medium temperature was varied in 1, 2, and 4 hours. The chemical activation used H3PO4. The ammonia concentration of simulated wastewater around 6000 mg/l. The acclimatization period was 8 d. The coconut shell ability for ammonia removal was observed after acclimatization period in 0, 2, 4, 6, and 8d.Â The effect of carbonization period and contact time on ammonia adsorption of dairy simulated wastewater was discussed in this research. This research used anaerobic digestion with 10 liter of volume. The concentration of ammonia was measured with nessler methods. Carbonization duration and contact time increased the adsorption capacity. From the obtained result of adsorption isotherm, the Langmuir equation was the best fit for all carbonization period, especially 4-hour carbonization period.